Left ventricular volume and ejection fraction determined by gated blood pool emission tomography. Issue 2 (February 1985) - Underwood, S R; Walton, S; Laming, P J; Jarritt, P H; Ell, P J; Emanuel, R W; Swanton, R H
Abstract : Electrocardiogram gated single photon emission computed tomography of the intracardiac blood pools is a recent development that involves the acquisition of images in multiple projections after in vivo erythrocyte labelling with technetium-99m and reconstruction of these images into tomographic sections in any desired plane. The technique was used in 25 subjects to measure left ventricular volume, by summing the areas of the ventricle in each of the tomographic sections, and the results compared with those using a counts based (non-geometric) technique from planar radionuclide ventriculography. Endocardium was defined with the aid of a contour at 43% of maximum left ventricular counts, and this contour was validated for a left ventricular phantom. Correlation between tomographic and counts based left ventricular volume was close. Similarly, ejection fraction correlated well. The technique is therefore an accurate method for determining left ventricular volume and ejection fraction, avoiding the assumptions about shape made by other geometric methods.